PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) PADA BERBAGAI PERSENTASE NAUNGAN - Kartika, Ramal Yusuf, Abd. Syakur, Ela (AGROTEKBIS, 2015)
The research was conducted in the Village Bulupountu Jaya, Sigi Biromaru Sub-District, Sigi District starting September to December 2014. The study was carried out to study and determine the effect of the percentage of shading on the growth and yield of tomato plants as well as a shading that is most appropriate percentage for the growth and yield of tomato plants. This research was conducted by using a randomized block design (RBD) with the percentage of shading consists of 6 level treatments, N0 = no shading, N1 = 10% shade, N2 = 20% shade, shade N3 = 30%, N4 = 40 shade, shade N5 = 50%. Each treatment was repeated three times so that there are 18 experimental units. The results showed that the various shading percentages significant effect on the plant height, number of leaves, the emergence of flower, fruit number and fruit weight of tomato (Lycopersicum esculentum Mill). The best growth and yield of tomato were treater with 30 % shade.